Duodenal occlusion for reticulosarcoma - Armand Ugon, Alfredo; Sáez, Hugo; Segura, Juan; Cagno, Carlos (Cirugía del Uruguay, 1977)
A patient suffered obstruction of the third secondary portian of duodenum and extrinsic compression due to reticulosarcomatose adenopathies. Gastroenteroanastomosis was performed.